2019
DOI: 10.12659/aot.915852
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pre-Procurement Pancreas Suitability Score (P-PASS) and Pancreas Donor Risk Index (PDRI) in the Outcome of Simultaneous Pancreas and Kidney or Pancreas After Kidney Transplantation

Abstract: Background The pre-procurement pancreas suitability score (P-PASS) and the pancreas donor risk index (pDRI) are established predictive scores for graft survival and patient outcome following pancreatic transplantation. This retrospective study aimed to evaluate the predictive value of P-PASS and pDRI following simultaneous pancreas and kidney (SPK) transplantation, or pancreas after kidney (PAK) transplantation, and the clinical impact of donor-specific factors on the postoperative graft and recip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
0
14
0
1
Order By: Relevance
“…This was handled by complete case analysis in all eight studies. Three studies had no missing data [ 34 , 38 , 41 ] and one study did not report missing data [ 45 ]. Graft failure was not defined in three studies (23%) [ 36 , 39 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This was handled by complete case analysis in all eight studies. Three studies had no missing data [ 34 , 38 , 41 ] and one study did not report missing data [ 45 ]. Graft failure was not defined in three studies (23%) [ 36 , 39 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…In these studies, PDRI was classified either as ‘high’ or ‘low’ according to the median PDRI within the cohort, or in tertiles. Furthermore, donor race was classified differently to that of PDRI derivation in one study due to differences in that country [ 36 ] and was not clearly classified in two studies [ 11 , 38 ] (not reported with other study variables). P-PASS was also validated while omitting serum sodium in one study due to lack of reporting in that jurisdiction [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 9 13 ] The 1- and 5-year patient survival rates after PTx are approximately 95% and 85%, respectively, and the 1-, and 5-year graft survival rates are 90%, and 70%, respectively. [ 10 , 13 , 14 ]…”
Section: Introductionmentioning
confidence: 99%